The revolutionists : the story of the extremists who hijacked the 1970s / Jason Burke. - Burke, Jason (The Bodley Head, 2025)
In the 1970s, a network of radical extremists terrorised the West with plane hijackings and hostage-takings. Among them were the beautiful young Leila Khaled with her jewellery made from grenade rings, the hard-drinking philanderer Carlos the Jackal sporting shades and open-neck shirts, and the radical leftists of the Baader-Meinhof Gang. They sought to liberate the Palestinians and overthrow western imperialism, orchestrating spectacularly violent attacks that held governments to ransom and the world gripped to their television screens. Drawing on decades of research, declassified archive material and original interviews with witnesses and participants, Jason Burke provides a masterful account of their exploits over the course of this dark decade.